2019
DOI: 10.25004/ijpsdr.2019.110107
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Evaluation of Tazarotene Solid Lipid Nanoparticles Gel for Topical Delivery

Abstract: The purpose of this research work was to develop and optimize the Solid Lipid Nanoparticles (SLNs) of Tazarotene for the effective topical delivery in the treatment of psoriasis. Tazarotene loaded SLNs were prepared by hot homogenization followed by the ultrasonication using Taguchi’s design and based on the results further investigation was made using central composite design. The lipid Dynasan-116, surfactant poloxomer-188 and co surfactant egg lecithin resulted in better percent drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…Lipids have been proposed as an alternative carrier to overcome the limitations of polymeric nanoparticles, especially for lipophilic pharmaceuticals. The formulation of Luliconazole as solid lipid nanoparticles also increases the drug's efficacy and exhibits a better therapeutic action 13,1 . Luliconazole-It is an antifungal agent belonging to imidazole group, which has a broad spectrum antifungal activity and has been shown to be effective against a wide range of fungi, especially dermatophytes.…”
Section: Drug Release Mechanism From Solid Lipidmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipids have been proposed as an alternative carrier to overcome the limitations of polymeric nanoparticles, especially for lipophilic pharmaceuticals. The formulation of Luliconazole as solid lipid nanoparticles also increases the drug's efficacy and exhibits a better therapeutic action 13,1 . Luliconazole-It is an antifungal agent belonging to imidazole group, which has a broad spectrum antifungal activity and has been shown to be effective against a wide range of fungi, especially dermatophytes.…”
Section: Drug Release Mechanism From Solid Lipidmentioning
confidence: 99%
“…Rheological parameters, in-vitro drug release, and permeation tests were carried out on the SLNbased gels. In-vitro antifungal studies revealed that an SLN-based drug was more effective in inhibiting the growth of Candida albicans and had a sustained release drug profile, implying that it could be used to treat topical fungal infections 13 . Shilpa N. Shrotriya et al, 2017 worked on Silybinloaded stable lipid nanoparticle-enhanced gel formulation and development for irritant contact dermatitis.…”
Section: Drug Release Mechanism From Solid Lipidmentioning
confidence: 99%
“…Solid lipid nanoparticles (SLNs) are biodegradable lipids with low toxicity [ 22 , 92 ] that can not only protect the constituents they incorporate from destruction, but can also be used as a means of transporting cosmetic agents into the stratum corneum since they can easily penetrate this layer [ 64 , 93 ]. SLNs can entrap various active compounds with several properties such as hydrophilic [ 94 ], lipophilic [ 95 ], or poorly water-soluble [ 96 ]. Furthermore, SLNs have better stability than liposomes as a result of being solid [ 97 ].…”
Section: Nanocarriersmentioning
confidence: 99%
“…The preparation method and physicochemical characteristics of the active agents can influence the efficiency of SLNs [ 100 ]. A study by Aland et al [ 96 ] demonstrated that a transdermal delivery formulation of tazarotene loaded into SLNs had better tolerability than the marketed formulation for the treatment of psoriasis. Indeed, the new formulation did not reveal any sign of skin irritation, showing an improvement in transdermal delivery of tazarotene.…”
Section: Nanocarriersmentioning
confidence: 99%
“…Add 2-3 drops of triethanolamine. As soon as, the triethanolamine is added the solution turns viscous and gel is formed [11].…”
Section: Preparation Of Sln Based Gelmentioning
confidence: 99%